Standar Operasional Prosedur Rekrutmen dan Pelatihan Pegawai Pada PT. Bank Perekonomian Rakyat Sumatera Selatan (Perseroda) - Franchika, Tri Mulia; Agustine, Grace Twenty; Revaldy, Adam (@-Publik: Jurnal Administrasi Publik, 2025)
Banks, as financial institutions, play a vital role in the economy, such as acting as intermediaries in collecting funds, distributing funds, and providing various services to the public. To support this, PT. Bank BPR Sumsel (Perseroda) has an effective strategy in managing human resources, particularly in the recruitment and training of employees. This study aims to analyze the implementation of Standard Operating Procedures for employee recruitment and training at PT. Bank BPR Sumatera Selatan (Perseroda). This study uses a descriptive qualitative method with a case study approach to explore an in-depth understanding of the implementation of Standard Operating Procedures in the employee recruitment and training process. The objectives of this study include: 1) to determine the standard operating procedures for employee recruitment and training implemented at PT. Bank BPR, 2) to determine the factors that influence the management of employee development or training programs at PT. Bank BPR Sumsel (Perseroda). Data was collected through interviews, observations, and documentation related to the procedures implemented. The results of the study show that the implementation of effective recruitment standard operating procedures can improve the quality of human resources recruited. Structured training standard operating procedures can improve employee competence and skills, thereby having a positive impact on company performance. This research provides practical contributions to PT. Bank BPR Sumsel (Perseroda) in optimizing the recruitment and training process through the implementation of clear and effective Standard Operating Procedures. Therefore, the implementation of Standard Operating Procedures in recruitment and training has a significant contribution to human resource development and the achievement of objectives in line with the vision and mission of PT. Bank BPR Sumsel (Perseroda). Therefore, the implementation of Standard Operating Procedures in recruitment and training has a significant contribution to human resource development and the achievement of objectives in line with the vision and mission of PT. Bank BPR Sumsel (Perseroda).